My "s" book - Moncure, Jane Belk.; Hohag, Linda; Moncure, Jane Belk. (Elgin, Ill. : Child's World ; Chicago, Ill. : Distributed by Childrens Press, 1984)
Little s goes for a walk along the sea and finds many things that begin with the letter "s" to put in his box.
Rev. ed. of: My s sound box. c1977.
Keywords: Alphabet